Kits for making women: Narratives and “imaginary” consumption of embodied music in La Mujer Album-Revista (1899-1902). (Revista Argentina de Musicología, 2010)
Taking into account the gendered nature of musical activity, the present paper attempts the analysis of discourse concerning professional women in musical theatre within texts from the weekly magazine La Mujer Álbum-Revista, published in Buenos Aires between 1899 and 1902. This exploration reveals how a series of implications and restrictions involving gender, influenced by the values of patriarchal hegemony, reach both the female bodies and the music itself. In this sense, discrimination regarding the value of opera, zarzuela, sainete or vaudeville is analyzed in the light of the relationship between music genre, female performing bodies and the narratives articulated around them.
Keywords: Gender; feminism; body; reception; narratives